Priority setting part two - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Japheth B Tugume, a district coordinator of the Bushenyi District Farmers Association in Uganda, talks of priority setting (see article above) as a question of attitude: 'I have always wondered why the perception of stakeholders is always targeted...